Basketball Players Undergoing Primary Hip Arthroscopy Exhibit Higher Grades of Acetabular Cartilage Damage but Achieve Favorable Midterm Outcomes and Return to Sports Rates Comparable With a Propensity-Matched Group of Other Cutting Sports Athletes. Issue 7 (June 2022) - Owens, Jade S.; Jimenez, Andrew E.; Lee, Michael S.; Hawkins, Gavin C.; Maldonado, David R.; Domb, Benjamin G.
Background: Favorable short-term outcomes in competitive basketball players have been reported. Midterm outcomes in these athletes and how they compare with athletes in sports with similar demands have not been well established. Purpose: (1) To report minimum 5-year patient-reported outcomes (PROs) and return to sports data in competitive basketball players undergoing primary hip arthroscopy for femoroacetabular impingement syndrome (FAIS) and (2) to compare outcomes with a propensity-matched control group of other cutting sports athletes. Study Design: Cohort study, Level of evidence, 3. Methods: Data were prospectively collected and retrospectively reviewed for basketball players who competed at the professional, collegiate, high school, or competitive amateur levels and underwent primary hip arthroscopy for FAIS between May 2009 and March 2016. Patients with preoperative and minimum 5-year postoperative outcomes for the modified Harris Hip Score (mHHS), Nonarthritic Hip Score (NAHS), Hip Outcome Score–Sports Specific Subscale (HOS-SSS), and visual analog scale (VAS) for pain were included. Patients were propensity matched to athletes in other cutting sports (soccer, lacrosse, field hockey, and tennis) according to age, sex, body mass index (BMI), and preoperative competition level for comparison. Results: A total of 28 competitive basketball players were included, with a mean follow-up time of 67.1 ± 5.1 months and a mean BMI of 23.7 ± 4; there were 12 (42.9%) female athletes. The cohort was composed of 1 professional, 10 collegiate, 13 high school, and 4 organized amateur athletes. They demonstrated significant improvements in all recorded PROs from baseline to the minimum 5-year follow-up ( P < .001) and had high rates of achieving the minimal clinically important difference (MCID) for the mHHS (75%), NAHS (75%), HOS-SSS (67.9%), and VAS for pain (71.4%). Furthermore, 76.5% of basketball players who returned to sports were still competing at a minimum of 5 years postoperatively. When compared with a propensity-matched cohort of other cutting athletes, basketball athletes demonstrated a significantly higher acetabular labrum articular disruption (ALAD) grade ( P < .001) and trended toward a higher Outerbridge grade of the acetabular cartilage ( P = .067). Despite this, basketball players demonstrated similar preoperative, postoperative, and improvement scores in all recorded PROs. Moreover, both groups exhibited similar rates of achieving psychometric thresholds and rates of continued sports participation at minimum 5-year follow-up. Conclusion: Competitive basketball players undergoing primary hip arthroscopy for FAIS demonstrated significant improvements in all recorded PROs and high rates of continued play at a minimum 5-year follow-up. When compared with a control group of other cutting sports athletes, basketball players exhibited more severe ALAD grades intraoperatively but similar midterm outcomes.